Fistulectomy in a 9-years old boy with pre-auricular fistula - Komang Soniananda Pradnyana Putri; Luh Witari Indrayani (DiscoverSys Inc., 2021)
Introduction: Preauricular fistule is a congenital malformation of the six auditory hillocks during the development of auricle. It mostly appears like a small pit close to the first ascending portion of the helix's anterior margin. The sebaceous glands secreted fluid through the opening of the fistule. Surgery is needed if the discharge is prolonged or if there was a repeated infection. It must be completely removed to prevent a recurrence. Accuracy is required in performing fistulectomy and aesthetics because the operation is in the area around the face.Case description: Male patient, 9 years old, complained of itching in the right ear. Since birth, the patient has an abnormal hole (fistule) in front of his right ear, anterior of the medial supra auricle helix, round and the size of a tip of the pencil. The mother has the same history. There is an abscess near that hole that secretes yellow pus. That occurred twice this year and it has greatly disturbed the patient's activities at school. The patient was diagnosed with a preauricular fistula with an abscess in the right ear. An abscess drainage incision was performed and an antibiotic was given. Fistulectomy is performed after the acute infection subsides under general anesthesia. The patient underwent a simple fistulectomy surgery. The whole track and sinus were removed, the defect was undermined and sutured.Conclusion: A simple fistulectomy is a good option as a standard procedure for preauricular fistula excision. It is especially useful as an alternative in cases where the other approaches are difficult to be performed.